2007
DOI: 10.1007/s10800-007-9450-x
|View full text |Cite
|
Sign up to set email alerts
|

Sonoelectrochemical (20 kHz) production of Co65Fe35 alloy nanoparticles from Aotani solutions

Abstract: This paper describes the production of alloy nanoparticles of Co:Fe ratio 65:35 from Aotani solutions in the presence of high power ultrasound (20 kHz). The production of this new type of alloy nanoparticles was performed potentiostatically and galvanostatically at (298 ± 1) K using a newly designed experimental set-up i.e. a 'sonoelectrode' producing short applied current pulses triggered and followed immediately by ultrasonic pulses. It was shown that cathode efficiencies decreased with increasing current de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…This new electrochemical method has since been employed to produce numerous pure metals [ 32 , 36 , 37 ] or alloys nanopowders [ 38 , 39 ] and semiconductor nanoparticles [ 40 ]. More recently, conductive polymer nanoparticles [ 41 ] have also been synthesized by pulsed sonoelectrochemistry.…”
Section: Experimental Devices and Methodologymentioning
confidence: 99%
“…This new electrochemical method has since been employed to produce numerous pure metals [ 32 , 36 , 37 ] or alloys nanopowders [ 38 , 39 ] and semiconductor nanoparticles [ 40 ]. More recently, conductive polymer nanoparticles [ 41 ] have also been synthesized by pulsed sonoelectrochemistry.…”
Section: Experimental Devices and Methodologymentioning
confidence: 99%
“…Dabalà et al [21] demonstrated the production of nanoparticles by sonoelectrochemistry as the technique offers many advantages: (i) great enhancement in mass-transport near the electrode, thereby altering the rate, and sometimes the mechanism, of the electrochemical reactions; (ii) modification of surface morphology through cavitation jets at the electrode-electrolyte interface, usually causing an increase of the surface area; and (iii) reduction of the electrode diffusion layer thickness and therefore ion depletion. Zin, Pollet, and Dabalà [22] modified Reisse's original setup by only using the vibrating tip of the ultrasonic probe as the cathode-'sonoelectrode', as shown in Figure 9.…”
Section: Sonoelectrochemical Production Of Pemfc and Pemwe Catalystsmentioning
confidence: 99%
“…Sonoelectrochemical setup for the production of PEMFC and PEMWE catalysts[17,21,22]. GC: Glassy carbon.…”
mentioning
confidence: 99%
“…Pulsed sonoelectrochemical techniques [78] have been employed to produce numerous pure metals [79,80], alloys [81], semiconductors [82] and polymer nanoparticles [83]. The particular attributes of metal powders obtained using this technology are that they are produced in a very finely divided state with high surface area, high chemical purity and with an average particle size of 100 nm [84].…”
Section: Nanomaterialsmentioning
confidence: 99%